Expanded Graphite (EG) Stabilization of Stearic and Palmitic Acid Mixture for Thermal Management of Photovoltaic Cells - Sereno Sacchet; Francesco Valentini; Alice Benin; Marco Guidolin; Riccardo Po; Luca Fambri (C, 2024)
In this work, passive cooling systems for the revamping of existent silicon photovoltaic (PV) cells were developed and analysed in order to mitigate the efficiency loss caused by temperature rise in the hot season. For this purpose, expanded graphite (EG) was used to stabilize a phase change material (PCM) with a melting temperature close to 53 °C in order to realize thermal management systems (TMSs) able to store heat at constant temperature during melting and releasing it in crystallization. In particular, stearic and palmitic acid mixture (PA-SA) was shape-stabilized in EG at different concentrations (10, 12 and 14 part per hundred ratio) under vacuum into a rotary evaporation apparatus followed by cold compaction; PA-SA leakage was reduced due to its intercalation between the graphite lamellae, and the thermal conductivity necessary to maximize the heat transfer to a bulk TMS was improved via powder cold compaction, which minimizes voids and creates preferential thermal conductive patterns. The composite materials, stable till 150 °C, were tested by differential scanning calorimetry (DSC) at 1 °C/min to precisely determine the phase transition temperatures and the enthalpic content, which was only slightly reduced from 196 J/g of the neat PCM to 169 J/g due to the very low EG fraction necessary for the stabilization. Despite only the 14:100 EG-to-PA-SA ratio, the system’s thermal conductivity was enhanced 40 times with respect to the neat PCM (from 0.2 to 8.3 W/(m K), value never reached in works present in the literature), with a good convergence of the values evaluated through hot disk tests and laser flash analysis (LFA), finding correlation with both graphitic content and density. In order to completely avoid leaking with the consequent dispersion of PCM in the environment during the final application, all the samples were encapsulated in a PE-made film. The mechanical properties were evaluated with compression tests at 30 °C and 80 °C simulating a possible compressive stress deriving from the contact needed to maintain the TMS position on the rear of the PV cells. Finally, the material response was simulated by imposing thermal cycles into a climatic chamber and reproducing the three hottest and coldest days of summer 2022 of two Italian locations, Verona (Veneto, 45° N, 11° E) and Gela (Sicily, 37° N, 14° E), thus highlighting the thermal management effects with delays in temperature increase and daily peak temperature smoothing. The role of EG is strategic for the processing and the properties of the resulting composites in order to realize a proper compromise between the melting enthalpy of PCM and the thermal conductivity enhancement given by EG.